Optical soliton solutions of the nonlinear complex Ginzburg-Landau equation with the generalized quadratic-cubic law nonlinearity having the chromatic dispersion - Esen, Handenur; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (IOP Publishing Ltd, 2024)
In this study, we consider the complex Ginzburg-Landau equation with the generalized quadratic-cubic law of self-phase modulation. This model finds applications in various fields, such as the study of superconductivity, nonlinear optical phenomena, pattern formation, and designing photonic devices and systems. This manuscript successfully employs the new Kudryashov method to derive analytical solutions for complex Ginzburg-Landau equations with the generalized quadratic-cubic law of self-phase modulation. The 3D, contour, and 2D graphical representations of the acquired solutions are represented. Therefore, W-shaped, bright, and dark soliton structures are derived. Through rigorous analysis and interpretation, valuable insights into the influence of the parameters of the presented model on the soliton behavior are achieved.
Keywords: Ginzburg-Landau model; quadratic-cubic law; self-phase modulation; soliton solutions; the new Kudryashov technique; WAVE SOLUTIONS; Physics